COVID-19 antibody tests: statistical implications. (2nd November 2020) - Kankam, Hadyn KN; Hourston, George JM; Ravindran, Pahalavi; Azhar, Bilal; Pope, Cassie
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has had significant implications for society, with the introduction of restrictive social measures. Antibody tests provide a way of identifying patients who have been previously exposed to the virus and thus may have a degree of immunity. This is important in the development of public health policy, as local and national bodies seek to relax social restrictions in an attempt to mitigate the socioeconomic impact of the pandemic. This article explores the essential statistical concepts used to interpret the findings of diagnostic investigations, with examples illustrated using COVID-19 antibody tests.